Understanding children's development. - Smith, Peter K.; Cowie, Helen; Blades, Mark (Wiley, 2015)
Revised to take account of developments in the field, this edition includes new discussion of the major issues in current UK and European research as well as expanded coverage of the practical applications of this research.